2012
DOI: 10.1158/0008-5472.can-11-2637
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T Cells Specific for Tumor Antigens Can Be Rendered Dysfunctional by the Tumor Microenvironment through Upregulation of the Inhibitory Receptors BTLA and PD-1

Abstract: Cytotoxic T cells that are present in tumors and capable of recognizing tumor epitopes are nevertheless generally impotent in eliciting tumor rejection. Thus, identifying the immune escape mechanisms responsible for inducing tumor-specific CD8+ T cell dysfunction may reveal effective strategies for immune therapy. The inhibitory receptors PD-1 and Tim-3 are known to negatively regulate CD8+ T cell responses directed against the well-characterized tumor antigen NY-ESO-1. Here, we report that the upregulation of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
248
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(266 citation statements)
references
References 25 publications
12
248
1
5
Order By: Relevance
“…These data extend and confirm previous observations that the activation and effector function of CD8 C T-cells correlates with the co-expression of multiple immune checkpoints. 25,[39][40][41][42] The frequency of PD-1 hi T-cells may therefore be useful as a surrogate marker for the functionality of TILs upon TCB activation as well as serve as a predictive marker for the therapeutic responses to TCB treatment. While this immune profile could guide the selection of patients who are likely to respond to immunotherapy such as TCBs, its correlation with in vivo Tcell exhaustion as a major therapy limiting component and clinical benefits remain to be determined in prospective clinical interventions.…”
Section: Discussionmentioning
confidence: 99%
“…These data extend and confirm previous observations that the activation and effector function of CD8 C T-cells correlates with the co-expression of multiple immune checkpoints. 25,[39][40][41][42] The frequency of PD-1 hi T-cells may therefore be useful as a surrogate marker for the functionality of TILs upon TCB activation as well as serve as a predictive marker for the therapeutic responses to TCB treatment. While this immune profile could guide the selection of patients who are likely to respond to immunotherapy such as TCBs, its correlation with in vivo Tcell exhaustion as a major therapy limiting component and clinical benefits remain to be determined in prospective clinical interventions.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 However, recent studies by other groups have found that BTLA may also promote cell survival by inducing a gene expression program similar to that induced by ICOS and CD28 costimulation. 8,9 Although BTLA has been characterized as a negative costimulatory molecule on T cells, a number of studies of human CD8 C T cells have shown that BTLA is constitutively expressed at a high level on na€ ıve CD8 C T cells and gradually downregulated during T-cell expansion and cytotoxic T lymphocyte (CTL) differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…6 Other negative checkpoint regulators expression on tumor-infiltrating lymphocytes, such as cytotoxic T lymphocyte antigen-4 (CTLA-4), lymphocyte activation gene-3 (LAG-3) and BTLA (B and T lymphocyte attenuator) also negatively regulate antitumor immunity in tumor microenvironments, the effects of co-blockage of them with Tim-3 still need further investigation. [21][22][23] Tim-3 and TIM-4 on TADC and TAM Despite Tim-3 and Tim-4 expressed by DCs and macrophages promote the phagocytosis of apoptotic cells through interaction with PS, little is known about what regulates Tim-3 and Tim-4 expression. Tumor microenvironments play a determinant role in tumor survival, suppressing responsiveness to anticancer drugs and accelerating subsequent tumor growth, thus may be responsible for the expression of Tim-3 and Tim-4 on tumor infiltrating cells.…”
Section: Introductionmentioning
confidence: 99%